Understanding the Adaptive Mechanisms of Plants to Enhance Phosphorus Use Efficiency on Podzolic Soils in Boreal Agroecosystems - Nadeem, Muhammad; Wu, Jiaxu; Ghaffari, Hamideh; Kedir, Amana Jemal; Saleem, Shamila; Mollier, Alain; Singh, Jaswinder; Cheema, Mumtaz (Frontiers in Plant Science, 2022)
Being a macronutrient, phosphorus (P) is the backbone to complete the plant growth cycle. However, due to low mobility and high fixation, P becomes the least available nutrient in podzolic soils; hence, enhancing phosphorus use efficiency (PUE) can play an important role in different cropping systems/crop production practices to meet the ever-increasing demands of food, fiber, and fuel. Additionally, the rapidly decreasing mineral phosphate rocks/stocks forced to explore alternative resources and methods to enhance PUE either through improved seed P reserves and their remobilization, P acquisition efficiency (PAE) or plant’s internal P utilization efficiency (IPUE) or both for sustainable P management strategies. The objective of this review article is to explore and document important domains to enhance PUE in crop plants grown on Podzol in the boreal agroecosystem. We have discussed P availabilities in podzolic soils, root architecture and morphology, root exudates, phosphate transporters and their role in P uptake, different contributors to enhance PAE, IPUE, and strategies to improve plant PUE in crops grown on podzolic soils deficient in P and acidic in nature.